Factors Cause Understanding Level of Low Soft Skill for Political Party Members and its Socialization Through Website - Sitompul, Roswita; Alesyanti, A; Hartono, H; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
This research is very urgent given the condition of our country today, where there are many anarchist actions, social conflicts, bad language and un-courtesy, and the lack of values, and culture. Indonesian people who are accustomed to behave in a manner, implement consensus in solving problems, have local wisdom that is rich with plurality, and tolerance and mutual cooperation begin to tend to be hegemonic groups that beat each other and behave dishonestly. All of this affirms that there is uncertainty of identity and character of the nation which leads to (1) disorientation and not yet fulfilled the values of Pancasila as the philosophy and ideology of the nation, (2) the limitations of integrated policy instruments in realizing the essence values of Pancasila, (3) (4) waning awareness of the nation's cultural values, (5) the threat of disintegration of the nation, and (6) the weakening of the nation's independence. Are not all these behaviors widely exhibited by this large political party in Indonesia and the Nationalist as the basis for the founding and the purpose of his party. The result of this research was expected to be known to many people through socialization by using the websiteÂ Â